Semantic Analysis of Lexical Units Expressing the Concept of “Person” in “Ravzatu-s-safo” - Kuryozova, Dilfuza (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2026)
This article examines the linguistic representation of the concept of "person" in the 15th-century historical chronicle Ravzatu-s-safo ("The Garden of Purity"). By analyzing terms such as insān, bashar, kas, and shakhs, this study elucidates how the author utilized a diverse lexical range to denote biological existence, social hierarchy, and moral agency. The research highlights the synthesis of Persian and Arabic vocabulary as a tool for historiographical precision and stylistic elevation.